Highly efficient room-temperature phosphorescence and afterglow luminescence from common organic fluorophores in 2D hybrid perovskites. Issue 48 (4th October 2018) - Yang, Shuming; Wu, Duobin; Gong, Wenjing; Huang, Qiuqin; Zhen, Hongyu; Ling, Qidan; Lin, Zhenghuan
Abstract : A simple and effective strategy on producing solution-processable materials with highly efficient and persistent room-temperature-phosphorescence (RTP) is presented here. Abstract : Regardless of rapid development of organic room-temperature phosphorescence (RTP) originating from phosphors in crystals, highly efficient and persistent RTP from common fluorophores is very rare. Herein, 1, 8-naphthalimide (NI), a common organic fluorophore, is doped into organic cations of 2D layered organic/inorganic hybrid perovskites (OIHPs) to yield thin films and powders with yellow RTP of NI in air. The triplet excitons of NI are mainly derived from Wannier excitons of inorganic perovskite through energy transfer (ET) for films, and from singlet excitons of NI through intersystem crossing (ISC) for powder. Consequently, the quantum yield ( Φ P ), lifetime ( τ ) and color of RTP can be tuned by changing the fluorophore and halide in the perovskites, as well as their solid morphology. A white emission, comprising the blue one from the perovskite and yellow RTP ( Φ P = 25.6%, τ = 6.3 ms) from NI, is obtained in Br-based OIHPs in powder. Cl-based OIHPs exhibit fluorescence/phosphorescence dual emission in thin films, and yellow afterglow phosphorescence in powders ( Φ P = 56.1%, τ = 35 ms). The unique performance of the OIHPs with RTP can make them widely applicable in the field of information technology as security ink, and white and afterglow LEDs as single luminescent materials.